Nail withdrawal properties on hybrid lamination board made from Sesendok (Endospermum Diadenum) and oil palm trunk (Elaeis Guineensis) / Siti Aishah Abu Bakar - Abu Bakar, Siti Aishah (Faculty of Applied Sciences, 2016)
In this study, withdrawal tests were carried out to determine the holding strength of nails on hybrid lamination board from wood and non-wood species. Sesendok (Endospermum diadenum) and Oil palm trunk (E!a;s gu;neens;s) were laminated using polyvinyl acetate (PVAc) glue. Sixty distinct samples were included in the study: thirty samples made of three layers, and thirty distinct samples made of five layers were tested and data were determined and compared. The dimensions of the samples were (50 x 50 x100) mm was prepared at ambient room temperature. Carbon metal type nails of sizes diameter and length at 2.9 x 69mm screw shank nail, 2.9 x 65mm ring shank nail, and 2.9 x 64mm common nail were used in the study. The data of withdrawal resistance of three types of nails were represented in maximum load, N. The nails were installed according to ASTM-D 1761 (2012) standards. Results show that the maximum nail withdrawal resistance value was found in screw shank nail for both three and five layer samples, followed by ring shank nails and then smooth shank nails. Between three types of nails, they are highly significant different strength. But, there were no significances different between three and five layers of samples